Is Urology a gender-biased career choice? A survey-based study of the Italian medical students' perception of specialties - Reale, Sofia; Orecchia, Luca; Ippoliti, Simona; Pletto, Simone; Pastore, Serena; Germani, Stefano; Nardi, Alessandra; Miano, Roberto (Frontiers in Surgery, 2022)
Background Despite the well-established worldwide phenomenon of “the feminisation of medicine,” in Italy, Urology remains a male-dominated field. Objective The aims of our work are to assess data on medical students' choice of surgical specialty in Italy to investigate if a gender-biased trend exists and to find the key points that influence the decision-making process when choosing a specialty, with a focus on Urology. Design Data about access to residency programs in 2017–2020 were analysed through descriptive statistics. Investigations concerning the decision-making process were carried through distribution of an online anonymous survey to Italian medical students. Results Urology was among the specialties with the lowest proportion of female residents in Italy in the last 4 years: 37 (29.4%) in 2017, 27 (21.4%) in 2018, 40 (26.7%) in 2019, and 57 (25.2%) in 2020. The total number of participants of the survey was 1409, of which only 341 declared being keen to pursue a career path in surgery. Out of the 942 students not interested in surgery, 46.2% females and 22.5% males indicated a “sexist environment” as one of the reasons. Overall, the main reason for medical students not choosing Urology is the lack of interest in the specialty. Furthermore, there is a different perception of Urology as a sexist environment between female (23.4%) and male (3.2%, p < 0.001) medical students, which may influence their decision-making process. Conclusions In Italy, the prevalence of female medical graduates does not mirror the proportion of female doctors choosing a career in some surgical specialties, including Urology. Our survey results clearly identified that a large proportion of medical graduates are not choosing urology because of the perception of a sexist environment. While the reasons for this phenomenon remain unclear, the presence of a gender-biased perception of a sexist environment represents a possible explanation.